Uji Aktivitas Campuran Minyak Kemiri dan Minyak Zaitun terhadap Panjang Rambut - Mercya, Yovita; Ramadani, Deshinta (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Candlenut oil and olive oil have been discovered to promote hair growth. This experimental study aimed to assess the effectiveness of a combination of candlenut oil and olive oil on the length of hair in male rabbits. The experiment involved two male rabbits, with four areas on their backs shaved to apply the test solution, each area measuring approximately 3 cm x 3 cm and spaced 2 cm apart. Hair samples were collected by shaving six strands of hair from each area on the 3rd, 6th, 9th, 12th, 15th, and 18th days. The treatment groups were divided into a negative control group that received no intervention and test groups that were treated with either candlenut oil alone, olive oil alone, or a combination of candlenut and olive oil. The results of the non-parametric Kruskal-Wallis test revealed a p-value of 0.000 (p ? 0.05), indicating a significant difference among the groups. A post hoc test was conducted to determine the group with the best hair length statistically, and it was found that the group receiving candlenut oil had the highest mean rank value, followed by the olive oil group, and then the combination of candlenut and olive oil group.